MANAJEMEN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SEKOLAH MENENGAH ATAS - Kurniawan, Agus Budi; Imron, Imron (Jurnal Isema : Islamic Educational Management, 2024)
The Pancasila Student Profile Strengthening Project is one of the activities in implementing the Merdeka Curriculum. The Pancasila Student Profile has the hope that graduates will be born with criteria that are characterized and skilled and their abilities are needed in the process of achieving in solidifying the noble values of Pancasila in that person. The hope of this can be achieved through project-based learning activities. This research aims to describe the Pancasila Student Profile Strengthening Project at Taruna Nusantara High School Magelang Central Java from planning, organizing, implementing, and monitoring and evaluating. Similar research conducted previously presents a general description of the implementation of P5, while this research presents more specific themes raised, namely Bangunlah Jiwa dan Raganya. The author used a qualitative approach to describe the management of P5 at Taruna Nusantara High School. The subjects of this study were the principal, vice principal of education, teachers, and students of Taruna Nusantara High School. The results obtained from this study are: (1) Project Planning (2) Organizing, (3) Implementation of Project (4) Project supervision is carried out by the principal, education vice-secretary, school supervisor, committee team and teachers then followed by an evaluation